Legal Protection for Debtors in Transactions Financing with Fiduciary Guarantee - Arafah, Arina Manasikana; Hanim, lathifah (TABELLIUS: Journal of Law, 2024)
This study aims to analyze: 1) Legal protection for debtors in financing transactions with fiduciary guarantees. 2) Obstacles and solutions in legal protection for debtors in financing transactions with fiduciary guarantees. This type of research is included in the scope of empirical legal research. The approach method in this study is a sociological juridical approach. The types and sources of data in this study are primary and secondary data obtained through interviews and literature studies. The analysis in this study is prescriptive. The results of the study concluded: 1) Legal protection for debtors in financing transactions with fiduciary guarantees aims to provide a sense of security and legal certainty for debtors in carrying out their obligations. Based on applicable legal provisions, the rights of debtors are protected through a fiduciary agreement that regulates the rights and obligations of each party. In this agreement, BPR BKK Demak as the lender is required to comply with applicable legal provisions regarding fiduciary guarantees, including fiduciary registration procedures so that the guarantee is legally valid. In addition, if the debtor experiences default or failure to pay, the BPR must execute the fiduciary guarantee in a manner that is in accordance with the procedure and does not violate the rights of the debtor. 2) Obstacles and solutions in legal protection for debtors in financing transactions with fiduciary guarantees Obstacles in legal protection for debtors in financing transactions with fiduciary guarantees include the lack of understanding of debtors regarding their rights and obligations, minimal supervision of the fiduciary guarantee registration process, and guarantee execution practices that are often not in accordance with procedures. These obstacles can cause legal uncertainty and unfair treatment for debtors. Solutions to overcome this problem include increasing education for debtors about their rights, stricter supervision from the government or supervisory institutions in fiduciary registration, and implementing guarantee execution standards that are in accordance with legal provisions.